AN ASSESSMENT ON THE RADIATION DOSE RECEIVED BY THE EYES AND THYROID USING PANAROMIC VIEW (OPG): A PHANTOM STUDY - SOHAIMI, NORHANNA; MAAROF, KHALIDAH (International Journal of Allied Health Sciences, 2020)
Introduction: The purpose of this paper is to assess on the radiation dose received by the eyes and thyroid on the panoramic view (OPG), using the phantom with the selected exposure setting based on the patient’s body habitus/size. Methods: Optically Stimulated Luminescence (OSL) dosimeters were placed on the three critical organs; right eye, left eye and thyroid and were exposed to the OPG machine at the Kulliyyah of Dentistry (KOD), International Islamic University, Malaysia (IIUM), Kuantan Campus. The Entrance Surface Doses (ESD) for each critical organ was measured at the Diagnostic Imaging Laboratory, Kulliyyah of Allied Health Sciences (KAHS), IIUM using the OSL reader. The means for each organ were recorded and the statistical analysis was done using the Kruskal-Wallis test to get the significant value for comparing these three organs/groups with selected exposure factor. Results: The overall means ± standard deviation (SD) for right eyes, left eyes and thyroid using the selected tube potentials of 62, 64, 66, 68 and 70 kVp were -3.62 ± 0.0058 µGy, -2.10 ± 0.0043 µGy and -3.09 ± 0.0042 µGy. The results were compared to other studies and the reference value or exposure limits from radiation protection organizations/boards. Conclusions: This study showed no statistical differences between the ESD for the critical organs when using different tube potentials (kVp) with p-value > 0.05. This indicates that the OPG exposure value was relatively lower in dose and produced almost negligible results in this experiment. When comparing this study from the results of other researches, the dose measurement in this study using the OPG equipment was the lowest and below the exposure limits in the radiation protection guidelines. However, further studies should be done using different OPG devices so that various significant and relevant results can be obtained and compared to the other studies. Therefore, this study might be a steppingstone for other studies to further for large scale extension study on radiation dose assessment of the critical organs in dental radiography. It is hoped that through this attempt, Malaysia might be able to produce and establish its own Diagnostic Reference Level (DRL) in dental radiography in the future.